Preparation method of nano deposited silicon negative electrode material based on activated carbon

By surface treatment and modification of nano-silicon and activated carbon, combined with conductive agents and other materials, an efficient nano-silicon anode material is prepared, which solves the problems of volume change and insufficient conductivity, and improves the stability and performance of lithium-ion batteries. .

CN119170771AInactive Publication Date: 2024-12-20SHENMU GUOPU ACTIVATED CARBON CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411326484.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The nano-silicon anode material based on activated carbon changes in volume during charging and discharging, resulting in damage to the electrode structure, affecting the cycle life and stability of the battery, and has poor electrical conductivity, which limits its application in lithium-ion batteries.

Method used

By depositing a protective film on the surface of nano-silicon, activated and modified activated carbon, combined with conductive agents, binders, carbon nanotubes and graphene, a negative electrode material containing 50%-60% activated carbon and 30%-40% nano-silicon was prepared. , high-speed stirring, solvent addition, coating, drying and rolling are used to form efficient conductive network and structural support.

Benefits of technology

It effectively reduces the side reaction between nano-silicon and electrolyte, improves the stability and cycle life of the material, enhances the conductivity and catalytic performance, alleviates the problem of volume changes, and improves the rate performance and charge and discharge efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170771A_ABST
    Figure CN119170771A_ABST
Patent Text Reader

Abstract

The invention relates to the field of chemical production, and discloses a preparation method of an activated carbon-based nano silicon deposition negative electrode material, which comprises the following steps: S1, preparing principles and pretreating: preparing activated carbon, nano silicon, a conductive agent, a binder and a carbon nanotube in proportion; the pretreatment comprises nano silicon surface treatment, activated carbon activation treatment and activated carbon modification treatment; s2, mixing and stirring: adding the pretreated nano silicon, activated carbon and carbon nanotubes into a high-speed stirrer, and stirring at first; according to the invention, surface treatment is carried out on the nano silicon, a layer of protective film is deposited on the surface of the nano silicon, side reaction between the nano silicon and electrolyte is effectively reduced, so that the stability and cycle life of the negative electrode material are improved, and meanwhile, activation treatment is carried out on the activated carbon, so that the specific surface area and porosity of the negative electrode material are increased, and the adsorption performance and conductivity are improved; a better conductive network and structural support are provided for the nanometer deposited silicon, and the problem of volume change of the nanometer deposited silicon in the charging and discharging process is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical production, and in particular to a method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon. Background Art

[0002] In today's society, the development of energy storage technology is crucial to meet the growing demand in areas such as electronic devices and electric vehicles. As an important energy storage method, the performance improvement of lithium-ion batteries has attracted much attention. At the same time, environmental protection issues are becoming increasingly severe. Sulfur oxides and nitrogen oxides in industrial waste gas cause serious pollution to the atmospheric environment.

[0003] The emergence of metal salt catalysts for desulfurization and denitrification and activated carbon with high desulfurization rate has provided an effective way to solve environmental problems. Activated carbon with high desulfurization rate can efficiently adsorb sulfides in exhaust gas due to its unique pore structure. In the field of energy storage, activated carbon has a high specific surface area and good conductivity. It is expected to combine its advantages with nano-silicon in the preparation of negative electrode materials for lithium-ion batteries and improve battery performance.

[0004] However, the current activated carbon-based nano-silicon anode materials still face many problems in preparation and application. The volume of nano-silicon changes greatly during the charge and discharge process, which can easily lead to damage to the electrode structure and affect the battery cycle life and stability. At the same time, nano-silicon has poor conductivity and has many side reactions with the electrolyte. These problems restrict its widespread application in lithium-ion batteries. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon, which solves the problem that the volume of the nano-silicon-precipitated negative electrode material of activated carbon changes greatly during the charge and discharge process, which easily leads to damage to the electrode structure and affects the battery cycle life and stability.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a nano-silicon-sinking negative electrode material based on activated carbon, including 50%-60% activated carbon, 30%-40% nano-silicon, 5%-8% conductive agent, 4%-6% binder, 4%-6% carbon nanotubes, and 2% graphene, wherein the conductive agent is specifically acetylene black, and the binder is specifically polyvinylidene fluoride.

[0007] A method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon comprises the following steps:

[0008] S1. Preparation principle and pretreatment: prepare activated carbon, nano-silicon, conductive agent, binder, and carbon nanotubes in proportion; pretreatment includes: nano-silicon surface treatment, activated carbon activation treatment, and activated carbon modification treatment;

[0009] S2. Mixing and stirring: The pretreated nano-silicon, activated carbon, carbon nanotubes and graphene are sequentially added to a high-speed mixer and stirred;

[0010] S3. Adding solvent: slowly adding an appropriate amount of solvent to the mixed material, the solvent including a conductive agent and a binder, and continuing stirring for a period of time to fully disperse the material in the solvent to form a uniform slurry;

[0011] S4. Coating and drying: The prepared slurry is evenly coated on the current collector such as copper foil, which can be coated by blade coating or extrusion coating. The thickness and uniformity of the coating are controlled to ensure the stable performance of the negative electrode material, and the coated material is placed in a drying oven for drying;

[0012] S5. Rolling and slicing: Rolling the dried negative electrode material to increase the density and compaction of the material, and cutting the rolled negative electrode material into sheets of a specific size as needed to facilitate battery assembly;

[0013] S6. Material packaging: Package qualified negative electrode materials in sealed bags or other packaging materials to prevent the materials from moisture, oxidation or contamination.

[0014] Preferably, in step S1, the surface treatment of the nano-silicon specifically includes: performing surface treatment on the nano-silicon in advance, and a thin protective film may be deposited on the surface of the nano-silicon by chemical vapor deposition.

[0015] Preferably, in step S1, the activated carbon activation treatment specifically includes: performing activation treatment on the activated carbon, using a physical or chemical activation method to increase the specific surface area and porosity of the activated carbon, and improve its adsorption performance and conductivity.

[0016] Preferably, in step S1, the activated carbon modification treatment is specifically: immersing the activated carbon in a solution containing a specific metal salt, and taking out the immersed activated carbon for drying and high-temperature treatment, so that the metal elements are evenly loaded on the surface and pores of the activated carbon.

[0017] Preferably, the protective film comprises a silicon dioxide layer to reduce side reactions with the electrolyte.

[0018] Preferably, the specific metal salt solution includes iron salt and cobalt salt.

[0019] Preferably, in step S2, the stirring speed of the stirrer is 1000-1500 rpm, and the stirring time is 2-3 hours.

[0020] Preferably, in step S3, the stirring speed of the stirrer is reduced to 500-800 rpm, and the stirring time is 1-2 hours.

[0021] Preferably, in step S4, the temperature of the drying oven is 80-120° C. and the drying time is 6-12 hours to completely evaporate the solvent.

[0022] The present invention provides a method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon.

[0023] Beneficial effects:

[0024] 1. The present invention treats the surface of nano-silicon and deposits a protective film, such as a silicon dioxide layer, on its surface, which effectively reduces the side reaction between nano-silicon and the electrolyte, thereby improving the stability and cycle life of the negative electrode material. At the same time, the activated carbon is activated to increase its specific surface area and porosity, improve adsorption performance and conductivity, provide a better conductive network and structural support for nano-silicon, and alleviate the problem of volume change of nano-silicon during charging and discharging.

[0025] 2. The present invention modifies the activated carbon, immerses the activated carbon in a solution containing a specific metal salt, such as an iron salt or a cobalt salt, and after drying and high-temperature treatment, uniformly loads the metal elements on the surface and in the pores of the activated carbon, further improving the conductivity and catalytic performance of the activated carbon. This helps to improve the electron transmission efficiency of the negative electrode material, and enhance the rate performance and charge and discharge efficiency of the battery.

[0026] 3. The present invention provides multiple groups of different ratios, including embodiment one, embodiment two, embodiment three and embodiment four, so that different embodiments are suitable for different use environments. Embodiment one focuses more on the capacity of the battery memory, embodiment two focuses more on the change of the battery appearance, embodiment three has better comprehensive performance, and embodiment four has the lowest cost and the highest cost performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a flow chart of the preparation method of the present invention;

[0028] Figure 2 The preparation principle and preprocessing flow chart of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] Please see attached Figure 1An embodiment of the present invention provides an activated carbon-based nano-silicon negative electrode material, including 60% activated carbon, 30% nano-silicon, 8% conductive agent, 4% binder, 4% carbon nanotubes, and 2% graphene.

[0032] The conductive agent is specifically acetylene black, and the binder is specifically polyvinylidene fluoride.

[0033] A method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon comprises the following steps:

[0034] S1. Preparation principle and pretreatment: prepare activated carbon, nano-silicon, conductive agent, binder, and carbon nanotubes in proportion;

[0035] Nano-silicon surface treatment: The nano-silicon is surface treated in advance. A thin protective film may be deposited on the surface of the nano-silicon by chemical vapor deposition, wherein the protective film includes a silicon dioxide layer to reduce the side reaction between the nano-silicon and the electrolyte.

[0036] Activated carbon activation treatment: Activate the activated carbon at the same time, using physical or chemical activation methods to increase the specific surface area and porosity of the activated carbon, and improve its adsorption performance and conductivity;

[0037] Activated carbon modification treatment: the activated carbon is immersed in a solution containing a specific metal salt, which includes iron salt and cobalt salt, and the activated carbon is taken out for drying and high-temperature treatment, so that the metal elements are evenly loaded on the surface and pores of the activated carbon;

[0038] S2 mixing and stirring: The pretreated nano-silicon, activated carbon, carbon nanotubes and graphene were sequentially added to a high-speed mixer and stirred first, the stirring speed of the mixer was 1000-1500 rpm, and the stirring time was 2-3 hours;

[0039] S3. Add solvent: slowly add an appropriate amount of solvent to the mixed material, the solvent includes a conductive agent and a binder, and continue stirring for a period of time to fully disperse the material in the solvent to form a uniform slurry. The stirring speed can be appropriately reduced to 500-800 rpm, and the stirring time is 1-2 hours;

[0040] S4. Coating and drying: Evenly coat the prepared slurry on the current collector such as copper foil, which can be coated by blade coating or extrusion coating. Control the coating thickness and uniformity to ensure the stable performance of the negative electrode material, and put the coated material into a drying oven for drying. The drying temperature and time should be determined according to the properties of the solvent and the thickness of the slurry. Dry at 80-120°C for 6-12 hours to completely evaporate the solvent;

[0041] S5. Rolling and slicing: Rolling the dried negative electrode material to increase the density and compaction of the material, and cutting the rolled negative electrode material into sheets of a specific size as needed to facilitate battery assembly;

[0042] S6. Material packaging: Package qualified negative electrode materials in sealed bags or other packaging materials to prevent the materials from moisture, oxidation or contamination.

[0043] Embodiment 1 Beneficial effects:

[0044] A high proportion of activated carbon provides structural support and conductive basis, nano-silicon ensures high capacity, acetylene black and graphene enhance conductivity, and carbon nanotubes adapt to volume changes. The overall performance is outstanding in terms of capacity and conductivity.

[0045] Embodiment 2:

[0046] The invention discloses an activated carbon-based nano-silicon-precipitated negative electrode material, comprising 62% activated carbon, 28% nano-silicon, 7% conductive agent, 5% binder, 2% silicon dioxide nanoparticles and 15% graphite.

[0047] The conductive agent is specifically SuperP, and the binder is specifically a mixed binder of sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0048] Embodiment 2 Beneficial effects:

[0049] More activated carbon ensures structural stability, a moderate proportion of nano-silicon reduces volume problems, SuperP conductive agent improves performance, silica nanoparticles reduce side reactions, and graphite reduces costs and alleviates volume changes.

[0050] Embodiment three:

[0051] A nano-silicon-precipitated negative electrode material based on activated carbon includes 63% activated carbon, 27% nano-silicon, 9% conductive agent, 4% binder, 3% carbon nanotubes, 1.5% silicon dioxide nanoparticles, 1.5% graphene and 10% graphite.

[0052] The conductive agent is specifically a mixed liquid of acetylene black and SuperP, and the binder is specifically a mixed binder of polyvinylidene fluoride and sodium carboxymethyl cellulose.

[0053] Embodiment 3 Beneficial effects:

[0054] The proportion of activated carbon is reasonable, nano-silicon reduces the volume impact while ensuring capacity, the mixed conductive agent combines the advantages to improve conductivity, and multiple materials work synergistically, with good overall performance in conductivity, volume change and cost control.

[0055] Embodiment 4:

[0056] A nano-silicon-precipitated negative electrode material based on activated carbon includes 65% activated carbon, 25% nano-silicon, 8% conductive agent, 4% binder, 1% silicon dioxide nanoparticles, 15% graphite and 2% carbon nanotubes.

[0057] The conductive agent is specifically conductive carbon black, and the binder is specifically polyimide.

[0058] Embodiment 4 Beneficial effects:

[0059] A high proportion of activated carbon ensures a stable structure, a low proportion of nano-silicon results in small volume changes, conductive carbon black reduces costs and ensures a certain conductivity, silica nanoparticles reduce side reactions, and graphite and carbon nanotubes synergistically improve performance, achieving a good balance between cost and performance.

[0060] Comparative experiment 1:

[0061] The performance of the four embodiments in terms of capacity retention and volume change mitigation was compared.

[0062] 2. Experimental Materials and Equipment

[0063] The negative electrode materials were prepared according to the formulations of the four embodiments.

[0064] Battery assembly materials such as positive electrode materials, electrolytes, and separators.

[0065] Battery assembly equipment.

[0066] Charge and discharge test equipment.

[0067] An instrument for measuring changes in volume (precision calipers).

[0068] 3. Experimental steps

[0069] Battery assembly: Prepare negative electrode materials according to the formulas of the four embodiments respectively, and assemble them into batteries with positive electrode materials, electrolytes, separators, etc. Ensure that at least 3 batteries are assembled for each embodiment to improve the accuracy of the test results.

[0070] Charge and discharge cycle test:

[0071] Set the parameters of the charge and discharge test equipment, such as charge current, discharge current, cut-off voltage, etc.

[0072] The battery of each embodiment is subjected to a charge and discharge cycle test, for example, 500 cycles are performed. During each cycle, the charge capacity and discharge capacity of the battery are recorded.

[0073] Volume change measurement:

[0074] During a specific stage of the battery's charge and discharge cycle testing, the thickness, length and width of the battery are measured using instruments such as precision calipers after every 100 cycles.

[0075] The volume change rate of the battery is calculated based on the measurement results.

[0076] 4. Experimental Results and Analysis

[0077] Battery capacity:

[0078] In the initial state, the average discharge capacity of Example 1 is 1000 mAh / g. After 500 cycles, the average discharge capacity drops to 850 mAh / g.

[0079] The initial average discharge capacity of Example 2 is 1000 mAh / g, and after 500 cycles it is 750 mAh / g.

[0080] The initial average discharge capacity of Example 3 is 1000 mAh / g, and after 500 cycles it is 800 mAh / g.

[0081] The initial average discharge capacity of Example 4 is 1000 mAh / g, and after 500 cycles it is 700 mAh / g.

[0082] Volume change:

[0083] After 500 cycles, the volume change rate of Example 1 is 20%.

[0084] The volume change rate of Example 2 is 15%.

[0085] The volume change rate of Example 3 is 18%.

[0086] The volume change rate of Example 4 is 22%.

[0087]

[0088] Experimental conclusion:

[0089] Through this comparative experiment, it can be seen that the average discharge capacity of the four embodiments in the initial state is 1000mAh / g, indicating that the embodiments have similar performance in terms of initial capacity. However, after 500 cycles, there are differences in the capacity retention and volume change rate of different embodiments.

[0090] The capacity retention of Example 1 is at a medium level, with an average discharge capacity of 850 mAh / g after 500 cycles, but the volume change rate is relatively high, at 20%. This shows that Example 1 has a greater advantage in capacity performance and is suitable for situations with large capacity requirements.

[0091] The capacity retention of Example 2 is relatively weak, and the average discharge capacity after 500 cycles is 750 mAh / g, but its volume change rate is relatively low, which is 15%. This shows that Example 2 performs well in controlling volume change and is suitable for use in an anti-deformation environment.

[0092] Example 3 is relatively balanced in terms of capacity retention and volume change. After 500 cycles, the average discharge capacity is 800 mAh / g and the volume change rate is 18%. Although the capacity change and volume change are not as good as those of Examples 1 and 2, it embodies the advantages of the synergistic effect of multiple materials and has better comprehensive performance.

[0093] The fourth embodiment has the worst performance in terms of capacity retention, with an average discharge capacity of 700 mAh / g and a volume change rate of 22% after 500 cycles. Although the fourth embodiment is inferior to the first, second and third embodiments in all aspects, the fourth embodiment uses conductive carbon black and a higher proportion of activated carbon, so the cost is relatively low and the cost performance is high.

[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nano-silicon-precipitated negative electrode material based on activated carbon, characterized in that: It includes 50%-60% activated carbon, 30%-40% nano silicon, 5%-8% conductive agent, 4%-6% binder, 4%-6% carbon nanotube, and 2% graphene, wherein the conductive agent is specifically acetylene black, and the binder is specifically polyvinylidene fluoride.

2. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 1, characterized in that: The following steps are involved: S1. Preparation principle and pretreatment: prepare activated carbon, nano-silicon, conductive agent, binder, and carbon nanotubes in proportion; Pretreatment includes: nano-silicon surface treatment, activated carbon activation treatment and activated carbon modification treatment; S2. Mixing and stirring: The pretreated nano-silicon, activated carbon, carbon nanotubes and graphene are sequentially added to a high-speed mixer and stirred; S3. Adding solvent: slowly adding an appropriate amount of solvent to the mixed material, the solvent including a conductive agent and a binder, and continuing stirring for a period of time to fully disperse the material in the solvent to form a uniform slurry; S4. Coating and drying: The prepared slurry is evenly coated on the current collector such as copper foil, which can be coated by blade coating or extrusion coating. The thickness and uniformity of the coating are controlled to ensure the stable performance of the negative electrode material, and the coated material is placed in a drying oven for drying; S5. Rolling and slicing: Rolling the dried negative electrode material to increase the density and compaction of the material, and cutting the rolled negative electrode material into sheets of a specific size as needed to facilitate battery assembly; S6. Material packaging: Package qualified negative electrode materials in sealed bags or other packaging materials to prevent the materials from moisture, oxidation or contamination.

3. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 1, characterized in that: In step S1, the surface treatment of the nano-silicon specifically includes: performing surface treatment on the nano-silicon in advance, and a thin protective film may be deposited on the surface of the nano-silicon by using a chemical vapor deposition method.

4. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 1, characterized in that: In step S1, the activated carbon activation treatment specifically includes: performing activation treatment on the activated carbon, using a physical or chemical activation method to increase the specific surface area and porosity of the activated carbon, and improve its adsorption performance and conductivity.

5. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 4, characterized in that: In step S1, the activated carbon modification treatment is specifically: immersing the activated carbon in a solution containing a specific metal salt, and taking out the immersed activated carbon for drying and high-temperature treatment, so that the metal elements are evenly loaded on the surface and pores of the activated carbon.

6. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 3, characterized in that: The protective film includes a silicon dioxide layer to reduce a side reaction between the protective film and the electrolyte.

7. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 5, characterized in that: The specific metal salt solution includes iron salt and cobalt salt.

8. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 2, characterized in that: In step S2, the stirring speed of the stirrer is 1000-1500 rpm, and the stirring time is 2-3 hours.

9. The method for preparing a nano-silicon-precipitated negative electrode material based on activated carbon according to claim 2, characterized in that: In step S3, the stirring speed of the stirrer is reduced to 500-800 rpm, and the stirring time is 1-2 hours.

10. The method for preparing a negative electrode material based on activated carbon nano-silicon deposition according to claim 2, characterized in that: In step S4, the temperature of the drying oven is 80-120° C. and the drying time is 6-12 hours to completely evaporate the solvent.

Citation Information

Patent Citations

  • Lithium ion battery silicon cathode material and preparation method thereof

    CN102709563A

  • Silicon-base cathode material for lithium ion battery and preparation method of silicon-base cathode material

    CN106711431A

  • Coconut shell-based mesoporous activated carbon, and preparation method and application thereof

    CN112938971A

  • Carbon-silicon composite material and preparation method and application thereof

    CN115117317A

  • Composite negative electrode material, preparation method thereof and battery

    CN118507721A